In the shoes of junior doctors: a qualitative exploration of job performance using the job-demands resources model - Chua, Jia Long; Mougammadou, Zeenathnisa; Lim, Raymond Boon Tar; Tung, Joshua Yi Min; Sng, Gerald Gui Ren (Frontiers in Psychology, 2024)
Background This qualitative study aimed to explore the factors affecting job performance amongst junior doctors working for public healthcare institutions in Singapore. Within these institutions, junior doctors experience challenges with maintaining a balance in job demands and resources, leading to strain. Exploring the lived experiences of these junior doctors is essential when reviewing workplace and organizational factors that contribute to stress on an individual level, providing valuable insights to address these challenges effectively. Method Semi-structured interviews were conducted with 20 junior doctors in Singapore, ranging from house officers to senior residents. Framework analysis was performed on transcribed de-identified interviews to identify themes deductively based on the Job Demands-Resources (JD-R) Model. Results Themes were identified and contextualized based on the exiting JD-R model. These themes shed light on how work demands, resources and personal factors influence the job performance of junior doctors and job satisfaction. Conclusion The study offers valuable insights into the specific issues disrupting the job demands and resource balance in Singapore Public Healthcare Institutions and their correlation with job performance. Our data suggests that job performance may be associated with job satisfaction. By understanding these factors, targeted efforts can be developed to improve working conditions for junior doctors, fostering their growth and engagement within the public healthcare system.